2021
DOI: 10.1111/jace.18286
|View full text |Cite
|
Sign up to set email alerts
|

Highly sensitive optical thermometer of Sm3+, Mn4+ activated LaGaO3 phosphor for the regulated thermal behavior

Abstract: Sm 3+ , Mn 4+ co-activated LaGaO 3 phosphors, giving the characteristic emissions of orange and red emission simultaneously, were prepared by a solid-state reaction. Their luminescence properties, energy transfer behavior, thermal stability, and ratiometric temperature sensing performance were investigated. Thanks to the inhibition of energy transfer between Sm 3+ and Mn 4+ ions at high temperature and the reconstruction of the traps, the distinct optical behavior of the involved activators dependent on the am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 40 publications
2
15
0
Order By: Relevance
“…Evidently, it is well fitted by the exponential formula: 40,41,42 FIRbadbreak=IasInormalsgoodbreak=Aexp()EnormalaknormalBTgoodbreak+B$$\begin{equation}{\mathrm{FIR}} = \frac{{{I}_{{\mathrm{as}}}}}{{{I}_{\mathrm{s}}}} = A\exp \left( {\frac{{ - {E}_{\mathrm{a}}}}{{{k}_{\mathrm{B}}T}}} \right) + B\end{equation}$$where I as is the intensity of Eu 3+ ions, I s is the intensity of host, A is the proportional parameter, k B is the Boltzmann constant, B is the offset parameter, and E a is the activation energy. The absolute sensitivity ( S a ) defined as the average FIR change with respect to T , and the relative sensitivity ( S r ), defined as the rate of FIR change along with T , can be expressed as: 37,43 Sabadbreak=Cexp()EnormalakTgoodbreak×()EnormalakT2$$\begin{equation}{S}_{\mathrm{a}} = C\exp \left( {\frac{{ - {E}_{\mathrm{a}}}}{{kT}}} \right) \times \left( {\frac{{ - {E}_{\mathrm{a}}}}{{k{T}^2}}} \right)\end{equation}$$ Sr=100%×Cexp()EnormalakT/0pt100%×Cexp()EnormalakT[]B+Cexp()EnormalakT×()EnormalakT20.0ptB+CexpEakT×EakT2<...…”
Section: Resultsmentioning
confidence: 99%
“…Evidently, it is well fitted by the exponential formula: 40,41,42 FIRbadbreak=IasInormalsgoodbreak=Aexp()EnormalaknormalBTgoodbreak+B$$\begin{equation}{\mathrm{FIR}} = \frac{{{I}_{{\mathrm{as}}}}}{{{I}_{\mathrm{s}}}} = A\exp \left( {\frac{{ - {E}_{\mathrm{a}}}}{{{k}_{\mathrm{B}}T}}} \right) + B\end{equation}$$where I as is the intensity of Eu 3+ ions, I s is the intensity of host, A is the proportional parameter, k B is the Boltzmann constant, B is the offset parameter, and E a is the activation energy. The absolute sensitivity ( S a ) defined as the average FIR change with respect to T , and the relative sensitivity ( S r ), defined as the rate of FIR change along with T , can be expressed as: 37,43 Sabadbreak=Cexp()EnormalakTgoodbreak×()EnormalakT2$$\begin{equation}{S}_{\mathrm{a}} = C\exp \left( {\frac{{ - {E}_{\mathrm{a}}}}{{kT}}} \right) \times \left( {\frac{{ - {E}_{\mathrm{a}}}}{{k{T}^2}}} \right)\end{equation}$$ Sr=100%×Cexp()EnormalakT/0pt100%×Cexp()EnormalakT[]B+Cexp()EnormalakT×()EnormalakT20.0ptB+CexpEakT×EakT2<...…”
Section: Resultsmentioning
confidence: 99%
“…The narrow bandwidth is typical of emission from the 2 E state, whose energy is largely insensitive to D and hence to Cr-O vibrations. Stokes and anti-Stokes bands can be attributed to either side of the 2 E peak [30].…”
Section: Photoluminescence Analysis Of Lagao3:cr 3+mentioning
confidence: 98%
“…LGO-based phosphors have been investigated previously for thermometric behaviour. Mondal et al synthesised LGO:Cr 3+ thermometers with a maximum LIR relative sensitivity of 2.07% K -1 at 150 K, and a temperature resolution of 0.24 K. [3] The LGO: Nd 3+ thermometers reported by Back et al had a maximum LIR relative sensitivity of 1.59% K -1 at 300 K and temperature resolution of ~1.0 K. [4] The Mn 4+ ion, like Cr 3+ , is a d 3 ion and has also been explored for luminescence thermometry, Li et al having reported a LGO: Sm 3+ , Mn 4+ material with a maximum relative sensitivity of 2.09% K -1 at 456 K [30]. Alongside Nd 3+ , vanadium can be used in dual emission luminescence thermometers, taking advantage of its various oxidation states, as in LaGaO3:V, Nd 3+ phosphors reported by Kniec et al Relative sensitivities for the V 5+ , V 4+ , and V 3+ -containing samples were, respectively, 1.0% K -1 at 268 K and 363 K; 0.49% K -1 at -293 K; and 1.44% K -1 at 348 K [31].…”
Section: Similarmentioning
confidence: 99%
“…A few studies have reported ratiometric thermometers for Sm(III) comprising phosphors. [69][70][71][72] Table 3 compares the reported sensitivities. SmAu in the broad T-range has good thermometric performance in comparison to other systems (Table 3) and a particularly good S r value for the low-temperature range.…”
Section: Optical Propertiesmentioning
confidence: 99%